Extracorporeal membrane oxygenation support following liver transplantation—A case series. Issue 7 (22nd June 2019) - Goussous, Naeem; Akbar, Hashem; LaMattina, John C.; Hanish, Steven I.; Barth, Rolf N.; Bruno, David A.
Abstract: Background: Postoperative severe cardiopulmonary failure carries a high rate of mortality. Extracorporeal membrane oxygenation (ECMO) can be used as a salvage therapy when conventional therapies fail. Methods: We retrospectively reviewed our experience with ECMO support in the early postoperative period after liver transplant between September 2011 and May 2016. Results: Out of 537 liver transplants performed at our institution, seven patients required ECMO support with a median age of 52 and a median MELD score of 28. Veno‐venous ECMO was used in four patients with severe respiratory failure while the rest required veno‐arterial ECMO for circulatory failure. The median time from transplant to cannulation was 3 days with a median duration of ECMO support of 7 days. All patients except one were successfully decannulated. The median hospital length of stay was 58 days with an in‐hospital mortality of 28.6%. Conclusion: Extracorporeal membrane oxygenation can be considered a viable rescue therapy in the setting of severe postoperative cardiopulmonary failure. Extracorporeal membrane oxygenation therapy was successful in saving patients who were otherwise unsalvageable.